Faktor-Faktor Yang Mempengaruhi Pengambilan Keputusan Wanita Berwirausaha Di Kota Surabaya - Pristiana, Ulfi; Kusumaningtyas, Amiartuti; Mujanah, Siti (Jurnal Riset Ekonomi dan Bisnis, 2009)
The aim of this research was to know what factors affected to the women decision making as enterprneur in Surabaya, and to answer to the research problem which is how is the internal dan eksternal factors affected to the women decision makingas as entrepreneur.Data gathering in this research was using survey method with questionair as instrument in this research. Responden in this research come from the women small enterprenuer populations, there was 150 women small enterprenuer choose by the purposif sampling technique. To answer the research problems dan test of hypothesis data was analyzed by using deskriptif analisis, Correlation, Regression F-test dan t-test.The result of the research show to us that the internal factors (interest, empowerment, and motivation) was affected to women in decision making as enterprneur especially interest and motivation, but the empowerment was not affected significantly. Furthermore eksternal factors such as the husband support and financial resource was not all affected but only the husband support was significantly affected. And the most dominant affected between those two variables was Motivation factor. Keywords: Interest, Empowerment, Motivation, Hasband Support, Capital Resources, Woman Decision Making, Interprneur